Exploring the oxidative mechanisms of bitumen after laboratory short- and long-term ageing. (28th June 2021) - Pipintakos, Georgios; Soenen, Hilde; Ching, H.Y. Vincent; Velde, Christophe Vande; Doorslaer, Sabine Van; Lemière, Filip; Varveri, Aikaterini; Van den bergh, Wim
Highlights: The oxidative mechanisms in bitumen were studied after laboratory short- and long-term ageing. Three binders of varying crude source, distillation, performance and wax presence were investigated. 1 H NMR demonstrated slight changes in the relative proton distribution upon ageing. EPR supported an increase of organic carbon-centred radicals after short-term ageing. TOF-SIMS revealed an increase of SOx -, (OH)x -containing compounds because of ageing. Abstract: Understanding the fundamental mechanisms of oxidative ageing in bitumen is considered of paramount importance in order to take steps towards durable binders able to tackle distresses related to this phenomenon which deteriorates the asphalt performance. This paper focuses on the identification of the intermediate and final oxygenated products after short- and long-term laboratory ageing simulated with rolling thin-film oven testing (RTFOT) and pressurised ageing vessel (PAV) respectively. Three binders were investigated in this study, two originated from the same wax-free crude source, while the third was obtained from a different source, containing natural wax, and followed a different manufacturing process. Fourier-Transform Infrared (FTIR) spectroscopy demonstrated a clear increase of the sulfoxide and carbonyl functional groups upon ageing for all the binders independently of origin, manufacturing or performance. Electron Paramagnetic Resonance (EPR) spectroscopy showed an increase of the organic carbon-centred radicals after short-term ageing (RTFOT), whereas after PAV these radicals remained constant in the two wax-free binders originating from the same crude source, and even decreased for the third, waxy binder. Proton Nuclear Magnetic Resonance ( 1 H NMR) spectroscopy reported differences in the relative distribution of protons between the binders in the unaged state, and similar minor changes after both ageing steps regardless of the binder's crude source and distillation. The results of Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) revealed that SOx - and (OH)x -containing compounds are produced after the sequentially occurring short- and long-term ageing in both wax-free bitumens, whereas an almost constant behaviour of aliphatics after PAV ageing can be seen for the same bitumens. Finally, the strengths and weaknesses of each of these experimental techniques were reviewed and compared versus the obtained results and possible ageing mechanisms.